2018
DOI: 10.1016/j.jretconser.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of customer acceptance of and resistance to smart technologies in the retail sector

Abstract: The rapid advancements in Internet technology have led to the development of numerous innovative smart technologies. This research investigates the customer acceptance and resistance of smart technologies in the retail sector by integrating the technology acceptance model, system characteristics, technology readiness, and store reputation literature. Data was collected using a quantitative survey and analysed using symmetrical PLS path modelling and asymmetrical fuzzy set qualitative comparative analysis (fsQC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
200
2
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(220 citation statements)
references
References 74 publications
10
200
2
8
Order By: Relevance
“…Ivanov et al [ 38 ] focused on the increased penetration of robots and AI in accommodation establishments and they explained that consumers’ attitudes towards the potential use of robots in hotels are largely driven by general attitudes which are built by the advantages of robots compared to humans. Roy et al [ 39 ] investigated the predictors of consumer attitude toward smart technologies in the retail sector. Their empirical test revealed the positive impact of the perceived ease of use and superior functionality which represents seamless experience on attitude.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Ivanov et al [ 38 ] focused on the increased penetration of robots and AI in accommodation establishments and they explained that consumers’ attitudes towards the potential use of robots in hotels are largely driven by general attitudes which are built by the advantages of robots compared to humans. Roy et al [ 39 ] investigated the predictors of consumer attitude toward smart technologies in the retail sector. Their empirical test revealed the positive impact of the perceived ease of use and superior functionality which represents seamless experience on attitude.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Furthermore, and more relevant to the theme of this special issue, this paper outlines a specific way of approaching the process of digitalisation, and the enactment of smart consumers. While there is now an emerging body of work within marketing and consumption studies, which is interested in smart consumers (Balaji & Roy, 2017) and the digitalisation of consumption more generally, much of this research has been geared towards either analysing cases in which smart technologies work (Balaji & Roy, 2017;Canhoto & Arp, 2017) or trying to determine barriers to the introduction and acceptance of smart technologies (Mani & Chouk, 2017;Roya, Balajib, Quazic, & Quaddus, 2018). In relation to this body of work, this study shows that our understanding of the opportunities and problems associated with smart consumers, and their making and makings, can be improved by understanding failures to enact smart consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Although in recent years there has been a plethora of studies on technology readiness and technology acceptance from the consumer's perspective, industrial context, or in the organizational adoption as a whole [5,10,14,[27][28][29][30][31][32][33][34][35][36][37], there is scarcity of research from an employee's perspective as the unit of analysis for readiness and technology acceptance [11,36,[38][39][40][41][42] in e-business environments. Moreover, no studies of such nature are found for technology intensive environments.…”
Section: Employees Customersmentioning
confidence: 99%